Development of efficient compositions of hydrophobic materials resistant to chemical and biological environments - Salman Dawood Salman Al-Dulaimi; S. I. Bazhenova; I. V. Stepina; I. V. Erofeeva; Victor Afonin (Journal of Infrastructure Preservation and Resilience)
Abstract In harsh or corrosive environments, waterproofing is essential for ground-contact structures. Protecting underground structures against groundwater contamination and moisture by waterproofing the base material, usually solid concrete, is beneficial. Long-term insulation system performance depends on component integrity and base material interaction. This study uses a hydraulically modified binder and finely ground construction waste fillers. Optimizing sealant and restoration is the goal. Additionally, this study will explore the characteristics and establish a systematic approach for determining the appropriate waterproofing system composition. The study measures the physical force required to remove the insulating layer in order to assess the adhesive strength of the sealant coating. This paper explains the theoretical conditions that improve the adhesion of the base- sealant sealing layer. A conceptual framework explains the relationship between sealant material adhesive strength, modified binder composition, and base surface moisture content. Empirical testing has proven this model works. A comprehensive study examined how base surface roughness and cracks affect sealant coating performance. We know the ideal strength factors. This study uses global optimization to examine optimized parameters' roles. This study analyzed experimental data statistically and analytically. According to computational analysis and experimental validation, the sealant material has an adhesive strength of 3.8 MPa and a sealant layer strength of 36–37 MPa. This product requires 3.9% acrylic resin, 80 kg/m3 finely broken concrete debris, and 0.38–0.39% plasticizer. For these components, a base surface with 9.7% to 9.8% moisture is ideal.